Treatment outcome of gartland type III supracondylar fracture humerus in children with closed reduction and percutaneous pinning - George, P. Thomas; Kattoor, Mithun Joy; Edayalamuriyil, Samson Samuel (International Journal of Research in Orthopaedics, 2016)
Background: Treatment of Gartland’s type III supracondylar fracture of humerus in children is one of the most challenging one. Conservative management usually results in deformity. On the other hand open reduction and internal fixation is a more invasive surgical method with a long recovery period. Thus, this study presents cases treated by closed reduction and percutaneous pinning and discussed its anatomical results, functional results and lastly its complications. Methods: Twenty five cases were treated with closed reduction and percutaneous pinning at Pushpagiri Medical College. Results: Out of the 25 patients studied, 24 (96%) had satisfactory results according to Modified Flynn’s criteria and there was only one case of superficial pin tract infection with no cases of cubitus varus deformity. Conclusions: This study presents that closed reduction and percutaneous pinning is a very good modality of treatment of Gartland type III fractures of humerus in children with very few complications.